2013
DOI: 10.1371/journal.pone.0049770
|View full text |Cite
|
Sign up to set email alerts
|

CO Rebinding Kinetics and Molecular Dynamics Simulations Highlight Dynamic Regulation of Internal Cavities in Human Cytoglobin

Abstract: Cytoglobin (Cygb) was recently discovered in the human genome and localized in different tissues. It was suggested to play tissue-specific protective roles, spanning from scavenging of reactive oxygen species in neurons to supplying oxygen to enzymes in fibroblasts. To shed light on the functioning of such versatile machinery, we have studied the processes supporting transport of gaseous heme ligands in Cygb. Carbon monoxide rebinding shows a complex kinetic pattern with several distinct reaction intermediates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
23
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 59 publications
5
23
0
Order By: Relevance
“…In these globins, CO dynamics between intraprotein cavities have been studied with lower time resolution (Ͼ10 ns). The temperature dependence of the small recombination phases on the submicrosecond time scale (the extent of which appears to correlate with the presence of an internal heme ligand (54)) also indicates virtually barrierless recombination toward the heme pocket and activated migration toward the solvent (55,56), with barriers on the same order of magnitude as found in the present work. Thus, whereas these studies do not cover the initial ligand migration steps, comparison with our work supports that these properties are general features of 6-coordinate heme proteins.…”
Section: Discussionsupporting
confidence: 76%
“…In these globins, CO dynamics between intraprotein cavities have been studied with lower time resolution (Ͼ10 ns). The temperature dependence of the small recombination phases on the submicrosecond time scale (the extent of which appears to correlate with the presence of an internal heme ligand (54)) also indicates virtually barrierless recombination toward the heme pocket and activated migration toward the solvent (55,56), with barriers on the same order of magnitude as found in the present work. Thus, whereas these studies do not cover the initial ligand migration steps, comparison with our work supports that these properties are general features of 6-coordinate heme proteins.…”
Section: Discussionsupporting
confidence: 76%
“…4) shows a pattern similar to the one observed for Ngb [146,162]. Photodissociated ligands can exit to the solvent following separate pathways, some of which exploit temporary docking sites [162] Hexacoordination by the distal His residue imposes large changes in energetic barriers that were suggested to modulate the flux of reactants to and products from the reaction site at the heme. Ligation appears to strongly affect CO rebinding kinetics to Cygb gels [162].…”
Section: Trapping Reaction Intermediates: Tertiary Relaxations and LImentioning
confidence: 60%
“…Photodissociated ligands can exit to the solvent following separate pathways, some of which exploit temporary docking sites [162] Hexacoordination by the distal His residue imposes large changes in energetic barriers that were suggested to modulate the flux of reactants to and products from the reaction site at the heme. Ligation appears to strongly affect CO rebinding kinetics to Cygb gels [162]. Cygb gels prepared by embedding unliganded Cygb (a bis-histidyl hexacoordinated species) allow easy formation of the CO adduct.…”
Section: Trapping Reaction Intermediates: Tertiary Relaxations and LImentioning
confidence: 99%
See 1 more Smart Citation
“…An increase in the geminate quantum yield was observed for Tyr44Phe and Tyr44Phe The observed heterogeneity was attributed to CO rebinding from primary and secondary ligand docking sites, as previously described in chapter 4 . Multiphasic kinetics has also been reported for CO geminate rebinding in Ngb and Cygb encapsulated in silica gels (Abbruzzetti et al, 2009;Gabba et al, 2013), but the fast rate constant reported here was not resolved in those studies.…”
Section: +mentioning
confidence: 52%